Repurposing the Whole Expression Transcriptome Assay for the Genetic Diagnosis of T-Cell Acute Lymphoblastic Leukemia and Lymphoma - Bardelli, Valentina; Arniani, Silvia; Pierini, Valentina; Nardelli, Carlotta; Matteucci, Caterina; Lema Fernandez, Anair Graciela; Crocioni, Maria; Cerrano, Marco; Salutari, Prassede; Papayanidis, Cristina; Trappolini, Silvia; Giglio, Fabio; et al. (The Journal of molecular diagnostics : JMD, 2025)
Unlike other cases of acute leukemia, the diagnosis of T-cell acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) is uniquely based on morphology and flow cytometry. Although the genomic background has been broadly uncovered, the large spectrum of genes involved and the variability of the molecular mechanisms underlying gene deregulation have delayed the introduction of molecular cytogenetics into diagnostic flowcharts. To overcome these limitations and implement a genetic diagnosis of T-ALL/LBLs, a whole transcriptome expression assay (WTEa) was repurposed as a "priority test" to classify T-ALL/LBLs into the major genetic subtypes. A WTEa classifier based on a set of 312 probes on 215 T-ALL/LBLs was set up and applied, which properly assigned >95% of cases with subtype-defining alterations to the corresponding subgroups (ie, TAL/LMO, HOXA, TLX1, TLX3, BCL11B). It pinpointed cases that harbored cryptic alterations, such as noncoding mutations that generate new enhancer at TAL1 and LMO2 loci (8% of TAL/LMO), and duplications of noncoding element downstream BCL11B (BETA) (18% of BCL11B). It was also suitable to classify lymphoma cases for which only formalin-fixed embedded tissues were available, as confirmed in cases harboring TLX1 or TLX3 rearrangements, and distinguished new putative subtypes. WTEa offers a unifying tool to provide a genetic classification of T-ALL/LBLs. If introduced in multicenter prospective studies, it will facilitate evaluation of the clinical impact of genetic classification.